Lesion localization of speech comprehension deficits in chronic aphasia. (7th March 2017) - Pillay, Sara B.; Binder, Jeffrey R.; Humphries, Colin; Gross, William L.; Book, Diane S.
Abstract : Objective: Voxel-based lesion-symptom mapping (VLSM) was used to localize impairments specific to multiword (phrase and sentence) spoken language comprehension. Methods: Participants were 51 right-handed patients with chronic left hemisphere stroke. They performed an auditory description naming (ADN) task requiring comprehension of a verbal description, an auditory sentence comprehension (ASC) task, and a picture naming (PN) task. Lesions were mapped using high-resolution MRI. VLSM analyses identified the lesion correlates of ADN and ASC impairment, first with no control measures, then adding PN impairment as a covariate to control for cognitive and language processes not specific to spoken language. Results: ADN and ASC deficits were associated with lesions in a distributed frontal-temporal parietal language network. When PN impairment was included as a covariate, both ADN and ASC deficits were specifically correlated with damage localized to the mid-to-posterior portion of the middle temporal gyrus (MTG). Conclusions: Damage to the mid-to-posterior MTG is associated with an inability to integrate multiword utterances during comprehension of spoken language. Impairment of this integration process likely underlies the speech comprehension deficits characteristic of Wernicke aphasia.